ORAI channels in cellular remodeling of cardiorespiratory disease. (May 2019) - Johnson, Martin; Trebak, Mohamed
Graphical abstract: Highlights: Cellular remodeling is a common theme in cardiorespiratory diseases. ORAI channels are calcium (Ca 2+ ) selective channels and have emerged as significant regulators of cellular remodeling during disease. This review details how dysregulation in ORAI channel expression and activation contributes to cellular remodeling in cardiorespiratory diseases. ORAI channels may be potential pharmaceutical targets in cardiorespiratory diseases. Abstract: Cardiorespiratory disease, which includes systemic arterial hypertension, restenosis, atherosclerosis, pulmonary arterial hypertension, asthma, and chronic obstructive pulmonary disease (COPD) are highly prevalent and devastating diseases with limited therapeutic modalities. A common pathophysiological theme to these diseases is cellular remodeling, which is contributed by changes in expression and activation of ion channels critical for either excitability or growth. Calcium (Ca 2+ ) signaling and specifically ORAI Ca 2+ channels have emerged as significant regulators of smooth muscle, endothelial, epithelial, platelet, and immune cell remodeling. This review details the dysregulation of ORAI in cardiorespiratory diseases, and how this dysregulation of ORAI contributes to cellular remodeling.